Integrating Sustainability in Urban Regeneration: Architectural Strategies and Policy Pathways in Developing Economies. - Alpana Kamble (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Urban regeneration in emerging economies is no longer solely about physical renewal; it represents a complex, multi-scalar challenge requiring systemic, sustainable, and inclusive approaches. This paper investigates how sustainable architecture when integrated with intelligent systems and participatory governance can act as a transformative catalyst for urban regeneration, particularly in India. Rapid urbanization, informal settlements, and climate-induced vulnerabilities necessitate a holistic approach that transcends conventional infrastructure-centric models. Using qualitative thematic analysis, the study synthesizes findings from academic literature, Indian urban policy frameworks (Smart Cities Mission, AMRUT, PMAY), and international case studies from Brazil, South Africa, and Southeast Asia. It identifies five core pillars of regenerative urbanism: institutional coordination, participatory design, architectural sustainability, innovative financing models, and robust impact assessment systems. The research highlights the potential of intelligent tools such as geospatial analytics, AI-based monitoring systems, and real-time governance dashboards to enhance decision-making and accountability. Comparative insights demonstrate that peer economies offer context-sensitive, scalable frameworks for inclusive regeneration. Key policy recommendations include establishing a National Urban Regeneration Council, empowering Urban Local Bodies (ULBs), mandating region-specific sustainable building codes, and institutionalizing community engagement mechanisms. By positioning sustainable architecture within a broader intelligent urban systems framework, the study proposes an integrated regeneration model that is climate-resilient, culturally anchored, and socially inclusive. The findings underscore India's potential to lead South-South collaborations in urban transformation by leveraging data-driven planning and design innovation.